Rye B chromosomes encode a functional Argonaute-like protein with in vitro slicer activities similar to its A chromosome paralog - Ma, Wei; Gabriel, Tobias Sebastian; Martis, Mihaela Maria; Gursinsky, Torsten; Schubert, Veit; Vrána, Jan; Doležel, Jaroslav; Grundlach, Heidrun; Altschmied, Lothar; Scholz, Uwe; Himmelbach, Axel; Behrens, Sven-Erik; et al. (The New phytologist, 2017)
B chromosomes (Bs) are supernumerary, dispensable parts of the nuclear genome, which appear in many different species of eukaryote. So far, Bs have been considered to be genetically inert elements without any functional genes. Our comparative transcriptome analysis and the detection of active RNA polymerase II (RNAPII) in the proximity of B chromatin demonstrate that the Bs of rye (Secale cereale) contribute to the transcriptome. In total, 1954 and 1218 B-derived transcripts with an open reading frame were expressed in generative and vegetative tissues, respectively. In addition to B-derived transposable element transcripts, a high percentage of short transcripts without detectable similarity to known proteins and gene fragments from A chromosomes (As) were found, suggesting an ongoing gene erosion process. In vitro analysis of the A- and B-encoded AGO4B protein variants demonstrated that both possess RNA slicer activity. These data demonstrate unambiguously the presence of a functional AGO4B gene on Bs and that these Bs carry both functional protein coding genes and pseudogene copies. Thus, B-encoded genes may provide an additional level of gene control and complexity in combination with their related A-located genes. Hence, physiological effects, associated with the presence of Bs, may partly be explained by the activity of B-located (pseudo)genes.
Keywords: B chromosomes; messenger RNA; buněčné jádro; Genes, Plant; Gene Amplification; Gene Expression Regulation, Plant; Computer Simulation; Gene Dosage; B-located genes; Gene Ontology; pseudogenization; počítačová simulace; DNA řízené RNA-polymerasy; rostlinné geny; Chromosomes, Plant; Chromatin; Secale cereale; Transcription, Genetic; DNA-Directed RNA Polymerases; genetická transkripce; rostlinné proteiny; Argonaute; Base Sequence; sekvence nukleotidů; Cell Nucleus; RNA, Messenger; gene expression; Plant Proteins; regulace genové exprese u rostlin; Argonaut proteiny; Secale; chromozomy rostlin; žito; chromatin; genová dávka; Argonaute Proteins; genová ontologie; gene erosion; amplifikace genu